An earliest Paleocene squirrelfish (Teleostei: Beryciformes: Holocentroidea) and its bearing on the timescale of holocentroid evolution. (1st January 2023) - Andrews, James V.; Schein, Jason P.; Friedman, Matt
Abstract : The record of articulated marine fish fossils during the latest Cretaceous and earliest Cenozoic is sparse. The oldest-known definitive squirrelfishes and soldierfishes, like the first examples of many extant reef-dwelling clades, are known from early Eocene deposits of Europe. Here, we describe a new genus and species of holocentroid (Teleostei: Beryciformes: Holocentroidea) based on material from three individuals from early Paleocene (Danian) deposits of New Jersey, USA using micro-computed tomography. The specimens comprise a three-dimensionally preserved skull and partial postcranium, plus two isolated neurocrania. The new taxon, † Iridopristis parrisi, possesses a unique combination of characters, including a heterosulcoid otolith morphology and an edentulous premaxillary tooth-gap, while lacking a newly proposed character for the remainder of Cenozoic holocentroids: a lamina on the lateral surface of the anguloarticular, anterior to the jaw joint. Bayesian phylogenetic analysis of morphological, stratigraphical and molecular data under the fossilized birth-death process finds that the new taxon branches from the holocentrid stem, where it is joined by two of the three squirrelfish genera from the early Eocene (Ypresian) of Bolca, Italy. We estimate a Danian divergence between Myripristinae and Holocentrinae, the two reciprocally monophyletic subfamilies of Holocentridae. Our analysis suggests that several holocentroid lineages crossed the Cretaceous–Palaeogene boundary. http://zoobank.org/urn:lsid:zoobank.org:pub:0B458336-EFCF-46D0-98D0-CE5AD371D7AF